2000
DOI: 10.4049/jimmunol.165.8.4606
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intracellular Chloride in the Reversible Activation of Neutrophil β2 Integrins: A Lesson from TNF Stimulation

Abstract: The process of β2 integrin activation, which enhances the interaction of these heterodimers with ligands, plays a crucial role in the adherence-dependent neutrophilic polymorphonuclear leukocytes’ (PMN) responses to TNF. Our previous observation, showing that a marked decrease of the high basal Cl− content (Cl−i) is an essential step in the TNF-induced activation of PMN, stimulated this study, which investigates the role of alterations of Cl−i in the activation of β2 integrins triggered by TNF. Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…The role of [Cl Ϫ ] i has been suggested as an important second messenger to regulate ␤ 2 integrin activation of polymorphonuclear leukocytes in response to tumor necrotic factor stimulation (22,23). Further work will be required to determine whether these changes in integrin and MMP expression reflect KCC-associated changes in [Cl Ϫ ] i or [K ϩ ] i or other functions of KCC possibly unrelated to ion transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of [Cl Ϫ ] i has been suggested as an important second messenger to regulate ␤ 2 integrin activation of polymorphonuclear leukocytes in response to tumor necrotic factor stimulation (22,23). Further work will be required to determine whether these changes in integrin and MMP expression reflect KCC-associated changes in [Cl Ϫ ] i or [K ϩ ] i or other functions of KCC possibly unrelated to ion transport.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of [Cl Ϫ ] i has been suggested as an important signal to regulate the activation of integrin in polymorphonuclear leukocytes (22,23). Although epithelial cells express a variety of cell adhesion molecules, integrins are the most important extracellular matrix receptors known to play a major role in the invasion and progression of most types of cancers (24).…”
Section: Suppression Of Tumor Growth and Invasion By ⌬ N 117 Mutant-wmentioning
confidence: 99%
“…Thrombin receptors activate chloride fluxes in megakaryocytes causing a rapid and immediate ion efflux following cell stimulation (56). Menegazzi and colleagues (33,57) have further identified a chloride efflux in polymorphonuclear lymphocytes that is directly and reversibly associated with ␤ 2 integrins and suggest a role for intracellular chloride ions as a second messenger in these cells. Interestingly, polymorphonuclear lymphocytes have been demonstrated to respond to activation with a fall in intracellular chloride concentrations and a corresponding integrin activation (33,57).…”
Section: Inhibition Of Platelet Function By the Putative Integrin Recmentioning
confidence: 99%
“…Menegazzi and colleagues (33,57) have further identified a chloride efflux in polymorphonuclear lymphocytes that is directly and reversibly associated with ␤ 2 integrins and suggest a role for intracellular chloride ions as a second messenger in these cells. Interestingly, polymorphonuclear lymphocytes have been demonstrated to respond to activation with a fall in intracellular chloride concentrations and a corresponding integrin activation (33,57). Although the authors did not identify which precise chloride channel was responsible for this alteration in chloride homeostasis, they demonstrated that its effect was specific for ␣ L and ␣ X integrins (containing KVGFFKR), not the ␣ M integrin (contains KLGFFKR).…”
Section: Inhibition Of Platelet Function By the Putative Integrin Recmentioning
confidence: 99%
See 1 more Smart Citation